The impact of a community health worker intervention on uptake of antenatal care: a cluster-randomized pragmatic trial in Dar es Salaam. Issue 3 (15th November 2022) - Regan, Mathilda; Cheng, Chao; Mboggo, Eric; Larson, Elysia; Lema, Irene Andrew; Magesa, Lucy; Machumi, Lameck; Ulenga, Nzovu; Sando, David; Mwanyika-Sando, Mary; Barnhart, Dale A; Hong, Biling; et al.
Abstract: The provision of high-quality antenatal care (ANC) is important for preventing maternal and newborn mortality and morbidity, but only around half of pregnant women in Tanzania attended four or more ANC visits in 2019. Although there is emerging evidence on the benefit of community health worker (CHW) interventions on ANC uptake, few large-scale pragmatic trials have been conducted. This pragmatic cluster-randomized trial, implemented directly through the public sector health system, assessed the impact of an intervention that trained public sector CHWs to promote the uptake of ANC. We randomized 60 administrative wards in Dar es Salaam to either a targeted CHW intervention or a standard of care. The impact of the intervention was assessed using generalized estimating equations with an independent working correlation matrix to account for clustering within wards. A total of 243 908 women were included in the analysis of our primary outcome of four or more ANC visits. The intervention significantly increased the likelihood of attending four or more ANC visits [relative risk (RR): 1.42; 95% confidence interval (CI): 1.05, 1.92] and had a modest beneficial effect on the total number of ANC visits (percent change: 7.7%; 95% CI: 0.2%, 15.5%). While slightly more women in the intervention arm attended ANC in their first trimester compared with the standard-of-care arm (19% vs 18.7%), the difference was not significant (RR: 1.02; 95% CI: 0.84, 1.22). Our findings suggest that trained CHWs can increase attendance of ANC visits in Dar es Salaam and similar settings. However, additional interventions appear necessary to promote the early initiation of ANC. This study demonstrates that routine health system data can be leveraged for outcome assessment in trials and programme evaluation and that the results are likely superior, both in terms of bias and precision, to data that are collected specifically for science.